2001
DOI: 10.1016/s0005-2736(00)00262-5
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol regulates membrane binding and aggregation by annexin 2 at submicromolar Ca 2+ concentration

Abstract: Annexin 2 is a member of the annexin family which has been implicated in calcium-regulated exocytosis. This contention is largely based on Ca(2+)-dependent binding of the protein to anionic phospholipids. However, annexin 2 was shown to be associated with chromaffin granules in the presence of EGTA. A fraction of this bound annexin 2 was released by methyl-beta-cyclodextrin, a reagent which depletes cholesterol from membranes. Restoration of the cholesterol content of chromaffin granule membranes with choleste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
64
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 47 publications
11
64
1
Order By: Relevance
“…It has been also reported that annexin A2 (21,22) and A2t (22) bind to phosphatidylinositol 4,5-bisphosphate (PtdIns(4,5)P 2 ) with high specificity and affinity and that this activity is linked to the organization of actin at membrane sites that are enriched in PtdIns(4,5)P 2 . Together with previous reports showing that annexin A2 binds cholesterol-containing membranes (23,24) and PtdIns(4,5)P 2 is localized in cholesterol-rich lipid rafts in the plasma membrane (25)(26)(27)(28), these results suggest that annexin A2 plays a role in regulating the formation of PtdIns(4,5)P 2 -rich lipid rafts or lipid raft-like structures. However, it is not known whether the annexin A2 dynamically controls the organization of these structures or it passively binds to the PtdIns(4,5)P 2 -rich regions.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…It has been also reported that annexin A2 (21,22) and A2t (22) bind to phosphatidylinositol 4,5-bisphosphate (PtdIns(4,5)P 2 ) with high specificity and affinity and that this activity is linked to the organization of actin at membrane sites that are enriched in PtdIns(4,5)P 2 . Together with previous reports showing that annexin A2 binds cholesterol-containing membranes (23,24) and PtdIns(4,5)P 2 is localized in cholesterol-rich lipid rafts in the plasma membrane (25)(26)(27)(28), these results suggest that annexin A2 plays a role in regulating the formation of PtdIns(4,5)P 2 -rich lipid rafts or lipid raft-like structures. However, it is not known whether the annexin A2 dynamically controls the organization of these structures or it passively binds to the PtdIns(4,5)P 2 -rich regions.…”
supporting
confidence: 86%
“…The K d value for this membrane is 27 nM even at 5 M Ca 2ϩ . Among various cellular membranes, the inner plasma membrane is known to contain the highest content of anionic lipids and cholesterol (see the footnotes to TABLE TWO), both of which have been shown to enhance the membrane affinity of annexin A2 and A2t (23,24). To further investigate the effect of cholesterol on the membrane affinity of A2t, we measured the binding of A2 to the plasma membrane mimetic without cholesterol.…”
Section: Resultsmentioning
confidence: 99%
“…Ax II has also been localized to adhesions between confluent Madin-Darby canine kidney cells (25). Ax II has been found to bind directly to anionic liposomes (11,12), and cholesterol has been reported to enhance this binding (26), suggesting that an Ax II/SHP-2 complex could bind directly to membrane lipid domains enriched in cholesterol. Membrane anchoring could also occur through an intrinsic membrane protein such as CD44, which was recently found to anchor Ax II to detergentresistant, cholesterol-rich membranes (rafts) in mammary epithelial EpH4 cells (27).…”
Section: Localization Of Shp-2 and Ax II To Adhesion Bands And Stressmentioning
confidence: 99%
“…Membrane anchoring could also occur through an intrinsic membrane protein such as CD44, which was recently found to anchor Ax II to detergentresistant, cholesterol-rich membranes (rafts) in mammary epithelial EpH4 cells (27). Both Ax II (27)(28)(29)(30) and SHP-2 (31) have been identified in rafts in cultured cells, and cholesterolsequestering reagents have been found to dissociate Ax II from both chromaffin granules (26) and endosomes (32). Alternatively, it is conceivable that the localization of either Ax II or SHP-2 to sites of cell-cell attachment could occur through direct binding to actin, since both Ax II (33,34) and SHP-2 (35) have been reported to bind to actin filaments in vitro, and both proteins were found along stress fibers in subconfluent endothelial cells (Fig.…”
Section: Localization Of Shp-2 and Ax II To Adhesion Bands And Stressmentioning
confidence: 99%
“…Addition of cholesterol to liposome enhances the ability of AIIt to bind with and aggregate phosphatidylserine vesicles at submicromolar Ca 2ϩ levels. Cholesterol also alters the subcellular localization of AIIt at low Ca 2ϩ concentrations (25,26). Arachidonic acid enhances AIIt-mediated fusion in model membranes (13).…”
mentioning
confidence: 99%